Instrumentation controlling as an important element of the enterprise's financial management system (Economics and region, 2018)
The essence and controlling tools in the financial management system of the company. On the basis of a comprehensive approach shaped architecture controlling. Generalized innovative for Ukrainian enterprises controlling concept, which allows to achieve maximum business success. Identified current trends in the introduction of controlling tools in the practice of domestic enterprises.
Keywords: controlling; controlling instruments; financial management; management accounting; are controlling functions